COVID-19 Testing and Tracking : Lessons Learned and a Look Ahead - Gandham, Ramana N.V.; Mutasa, Ronald; Mohammed, Suresh Kunhi; Jammy, Guru Rajesh; Bhatnagar, Aarushi (World Bank, Washington, DC, 2021)
The COVID-19 pandemic has ravaged the global economy, either reversing or slowing ongoing efforts to eliminate extreme poverty in many countries. Despite recent progress, including increased recoveries and lower death rates, India is ranked third globally in absolute numbers of COVID-19 reported cases. India’s chronic underinvestment in health, coupled with a hard-hit economic sector, has further entrenched segments of India’s population in vulnerability and poverty. The exodus of millions of migrants from the cities has contributed to the spread of infection from urban to rural areas, where health systems are weaker. As economic activities are revived following a period of lockdowns, policy makers must make smart choices that prevent and rein in the spread of COVID-19. In the absence of effective treatment and a vaccine, preventive measures combined with testing and tracing, followed by quarantine and isolation and supportive treatment, are critical to minimize the spread of COVID-19 and rejuvenate livelihoods to restore India’s economy. In this paper, authors bring together promising testing and tracing lessons and approaches from India and globally, based on a desk review of various initiatives and analyses of secondary data. Key lessons and findings are that: (i) testing and tracing is central to an effective COVID-19 response; (ii) a robust response to an unprecedented pandemic requires creative approaches, such as active case finding, pooled testing, testing environmental samples, triangulation of microdata, effective contact tracing, and partnering with the private sector; (iii) optimizing COVID-19 testing capacity should not negatively impact ongoing disease control programs; (iv) containment of COVID-19 should go hand-in-hand with preparation for future pandemics. We also summarize innovations and bottlenecks to rapidly scale up testing capacities at the state level, including strategies for optimizing the role of the private sector and introducing new technologies to enhance access to testing in rural populations. This paper offers options especially relevant to Indian policy makers, with a focus on sustained health systems strengthening.